TiO2-Au plasmonic nanocomposite for enhanced dye-sensitized solar cell (DSSC) performance - Muduli, Subas; Game, Onkar S.; Dhas, Vivek V.; Vijayamohanan, K.; Bogle, Kashinath A.; Valanoor, N.; Ogale, Satishchandra B. (Solar Energy, 2012)
Anatase TiO2 nanoparticles dressed with gold nanoparticles were synthesized by hydrothermal process by using mixed precursor and controlled conditions. Diffused Reflectance Spectra (DRS) reveal that in addition to the expected TiO2 interband absorption below 360 nm gold surface plasmon feature occurs near 564 nm. It is shown that the dye sensitized solar cells made using TiO2-Au plasmonic nanocomposite yield superior performance with conversion efficiency (CE) of similar to 6% (no light harvesting), current density (J(SC)) of similar to 13.2 mA/cm(2), open circuit voltage (V-oc) of similar to 0.74 V and fill factor (FF) 0.61; considerably better than that with only TiO2 nanoparticles (CE similar to 5%, J(SC) similar to 12.6 mA/cm(2), V-oc similar to 0.70 V, FF similar to 0.56). (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Anatase TiO2; Au; Dye-sensitized solar cells; Hybrid composite; hydrothermal